Interplay between Carotenoids, Abscisic Acid and Jasmonate Guides the Compatible Rice-Meloidogyne graminicola Interaction - Kyndt, Tina; Nahar, Kamrun; Haeck, Ashley; Verbeek, Ruben; Demeestere, Kristof; Gheysen, Godelieve (Frontiers in Plant Science, 2017)
In this study, we have characterized the role of carotenoids and chlorophyll in the compatible interaction between the sedentary root knot nematode (RKN) Meloidogyne graminicola and the monocot model plant rice (Oryza sativa). Previous transcriptome data showed a differential expression of carotenoid and chlorophyll biosynthesis genes in nematode-induced giant cells and gall tissue. Metabolite measurement showed that galls indeed accumulate chlorophyll a, b and carotenoids, as well as the hormone abscisic acid (ABA). When ABA was externally applied on rice plants, or when ABA-biosynthesis was inhibited, a significant increase in gall formation and nematode development was found, showing the complex role of ABA in this interaction. ABA application suppressed jasmonic acid (JA) levels in the plants, while ABA-biosynthesis inhibition lead to increased JA levels confirming an antagonism between ABA and JA in rice roots. In addition, combined applications of ABA and JA showed that the ABA-effect can overcome JA-induced defence. Based on these observations, we hypothesized that the accumulation of chlorophyll and carotenoid precursors would be beneficial to nematode infection. Indeed, when chemically blocking the carotenoid biosynthesis pathway at different steps, which leads to differential accumulation of carotenoids and chlorophyll in the plants, a positive and clear link between accumulation of carotenoids and chlorophyll and rice susceptibility to RKN was detected.